2012
DOI: 10.2187/bss.26.7
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Resistance of Caenorhabditis elegans Against High-LET Radiation Exposure

Abstract: Effects of high linear energy transfer (LET) radiation on the functions of the nervous system is a potential risk in interplanetary manned space missions. However, little is known about how the ner vous system is protected against high-LET radiation exposure. The analysis of high-LET radiation resistant animals would be therefore important for space missions. Here, we investigated the resistance to high-LET radiation exposure for two behaviors of the nematode, Caenorhabditis elegans, which is known as a model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…Locomotory behavior is vital for securing food and escaping from harmful environments. Previous experiments showed that motility (locomotion) in the nematode Caenorhabditis elegans was reduced by whole-body irradiation with either gamma rays or carbon ions, in a dose-dependent manner [ 1 3 ]. Furthermore, hydrogen peroxide, which is a reactive oxygen species (ROS) produced by radiation exposure, was shown to be potentially involved in this reduced motility [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Locomotory behavior is vital for securing food and escaping from harmful environments. Previous experiments showed that motility (locomotion) in the nematode Caenorhabditis elegans was reduced by whole-body irradiation with either gamma rays or carbon ions, in a dose-dependent manner [ 1 3 ]. Furthermore, hydrogen peroxide, which is a reactive oxygen species (ROS) produced by radiation exposure, was shown to be potentially involved in this reduced motility [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that chemotaxis to NaCl is highly resistant to low-and high-LET irradiation even at 1,000 Gy (Sakashita et al, 2012). However, the SCL ability was completely lost after low-LET irradiation at 1,000 Gy (Sakashita et al 2008b), and this was indeed the case for high-LET irradiation at 1,000 Gy (Fig.…”
Section: Dose Response For the Scl Abilitymentioning
confidence: 57%
“…BioMed Research International functions are important for space missions. The effects of high-LET radiation exposure on several behaviors including muscle movements have been investigated using the nematode C. elegans [66,67,69,153,154], which is an experimental model organism and a powerful tool to study the effects of radiation. In this animal, locomotion, including forward and backward movements and turns, is carried out by 95 body wall muscle cells, for which the fate of each cell from its birth to death can be easily determined.…”
Section: Genome Instabilitymentioning
confidence: 99%
“…In this animal, locomotion, including forward and backward movements and turns, is carried out by 95 body wall muscle cells, for which the fate of each cell from its birth to death can be easily determined. Locomotion (motility) of adult C. elegans on an agar plate without food was reported to decrease in a dose-dependent manner immediately after whole-body irradiation was administered using both high-LET radiation ( 12 C, 18.3 MeV/u, LET = 113 keV/μm) [67,153] and low-LET radiation ( 60 Co γ-rays) [155]. The RBE ratio of high-LET radiation relative to low-LET radiation for inhibition of locomotion was 1.4 [153].…”
Section: Genome Instabilitymentioning
confidence: 99%
See 1 more Smart Citation